A new genus and new species of soft coral (Octocorallia: Alcyonacea: Alcyoniidae) from the south western region of Australia - Alderslade, P. (Zootaxa, 2003)
Notodysiferus dhondtae new genus & new species (Octocorallia: Alcyoniidae) is described from King George Sound, Albany, Western Australia. The shallow water, dimorphic, zooxanthellate genus has a massive, encrusting growth form similar to some species of warm water alcyoniid genera such as Sinularia and Lobophytum. The new taxon has both autozooids and siphonozooids in most of the area of the lobes of the polypary, but siphonozooids alone are distributed over the basal regions of the lobes. The sclerites of the new taxon are 8-radiate capstans and their derivatives. Remarks are presented on the alcyonacean fauna of the region, and the new genus is compared to similar taxa.